Two new species of eriophyid mites (Acari: Eriophyidae) from India - Menon, Pratibha; Joshi, Sushila; Ramamurthy, V. V. (Zootaxa, 2009)
Two new species of eriophyid mites (Acari: Prostigmata) viz. Cosetacus sharadi n. sp., collected from leaf erineum on Cordia dichotoma (Boraginaceae), and Acalitus delhiensis n. sp., collected from leaf erineum on Salvadora persica (Salvadoraceae), are described from India. Cosetacus sharadi has divided feather claw, each branch comprising of 4–5 rays, shield with median line present from rear to mid, admedian lines parallel to median line till mid, then bulging out meeting at the anterior end, submedian lines present from anterior to mid, epigynium ribbed in 2 ranks, accessory seta absent, antapical seta present. Acalitus delhiensis has 7 rayed simple feather claw, shield with median line present in rear to mid, admedian and submedian lines branched, epigynium coarsely granulated, accessory seta and antapical seta absent.